Designing a Website-Based Bus Ticketing System for Ria Sari Bus Agents - Novita, Stefani Arfiyani; Harnadi, Bernardinus; Koeswoyo, G. Freddy (Journal of Business and Technology, 2024)
Ria Sari Bus Ticket Agent is a night ticket agent that serves the various regions in Indonesia. Currently, the agent still uses a manual system to record bus ticket sales. Agents still write prospective passenger data and calculate agent commissions manually. In addition, sometimes agents forget about passenger orders that have been booked long ago. This usually happens during the Eid season and long vacations. This bus agent also does not have a recap of sales reports every month, so it does not know the commission earned each month. This study has a solution in a website-based ticket sales information system developed using Laravel, PHP, XAMPP, and MySQL. The purpose of the study is to design and develop a website-based bus ticketing system for Ria Sari Bus Ticket Agent. The testing of the system is conducted by interviews with the owner and users of the system. The result shows all features and menus available in this system are working properly and in accordance with the access rights of each user. The owner and users are satisfied and perceived helpful in using the system.